2010
DOI: 10.1017/s0144686x10000656
|View full text |Cite
|
Sign up to set email alerts
|

In home or at home? How collective decision making in a new care facility enhances social interaction and wellbeing amongst older adults

Abstract: Benevolent, long-term care can threaten older adults' sense of autonomy in a residential home environment. Increasing reliance on a hotel style of living has been seen to erode social identity, life satisfaction and even survival or lifespan. Drawing on evidence from both gerontological and social psychological literature, this paper examines the links between the empowerment of residents and their subsequent quality of life in the context of a move into a new care facility in a medium-sized town in South-West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 93 publications
3
68
0
1
Order By: Relevance
“…Most clearly, MS patients (particularly those with Relapsing-Remitting and Primary Progressive MS) should be encouraged to engage with support groups, but more must be done to ensure they subjectively identify with these support groups (rather than simply attend them). Previous work has shown that giving group members a sense of collective agency over decisions regarding the group's development (such as deciding how to decorate the group's interaction space) enables group identification to develop, so such initiatives may prove fruitful in the current context [43].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Most clearly, MS patients (particularly those with Relapsing-Remitting and Primary Progressive MS) should be encouraged to engage with support groups, but more must be done to ensure they subjectively identify with these support groups (rather than simply attend them). Previous work has shown that giving group members a sense of collective agency over decisions regarding the group's development (such as deciding how to decorate the group's interaction space) enables group identification to develop, so such initiatives may prove fruitful in the current context [43].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…By contrast, research in subjective wellbeing suggests that much more depends on improving the social context than on the delivery of specific services. The best illustration of this, and one that dovetails nicely with the Singapore Prison reforms, is provided by the elder-care experiments of Knight, Haslam and Haslam (2010). When residents of an elder-care facility were being moved to a new building, the control group (the residents of the previously happier floor in the old facility) were given the best of professional designs for their new shared spaces, while the experimental group were invited to get together to make their own design decisions.…”
Section: Process Mattersmentioning
confidence: 99%
“…Achieving the latter does not necessarily need to be overly complex or costly: Knight et al (2010) found that both group identification and SWL were enhanced for elderly care-home residents who were able to make collective decisions regarding how to decorate their living-space (versus those who were not).…”
Section: Implications and Conclusionmentioning
confidence: 99%